2010
DOI: 10.1111/j.1751-7176.2010.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Therapy for Resistant Hypertension: Simplifying the Approach

Abstract: Despite the availability of many effective antihypertensive drugs, the drug therapy for resistant hypertension remains a prominent problem. Reviews offer only the general recommendations of increasing dosage and adding drugs, offering clinicians little guidance with respect to the specifics of selecting medications and dosages. A simplified decision tree for drug selection that would be effective in most cases is needed. This review proposes such an approach. The approach is mechanism‐based, targeting treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 79 publications
(135 reference statements)
0
27
1
2
Order By: Relevance
“…11) Previous reports revealed the ineffectiveness of an adequate dose of an ACE inhibitor/diuretic or ARB/diuretic combination in resistant hypertension. 11,13) Acelajado, et al reported that greater sympathetic output based on higher heart rates may be contributing to antihypertensive treatment failure in resistant hypertension. 14) However, few data from randomized trials are available to guide the choice of beta blockers for resistant hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…11) Previous reports revealed the ineffectiveness of an adequate dose of an ACE inhibitor/diuretic or ARB/diuretic combination in resistant hypertension. 11,13) Acelajado, et al reported that greater sympathetic output based on higher heart rates may be contributing to antihypertensive treatment failure in resistant hypertension. 14) However, few data from randomized trials are available to guide the choice of beta blockers for resistant hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…General algorithms have been proposed. One such interesting proposal advocates a mechanism-based, multiple-drug regimen targeting treatment at the three hypertensive mechanisms: sodium/volume, RAAS, and SNA [45]. Such a regimen starts with baseline treatment with a two-drug combination directed at sodium/volume and the RAAS.…”
Section: Combination Therapiesmentioning
confidence: 98%
“…1. Algorithm of diagnosing resistant hypertension [10] A drug regimen should be based on combination therapy, taking into account the basic mechanisms conditioning arterial hypertension development, such as sodium metabolism/volemia, renin-angiotensin-aldosterone system (RAAS) and increased tension of the sympathetic nervous system [34]. Most clinical trials involved dual therapy, with particular emphasis on diuretic treatment [2].…”
Section: Treatment Of Resistant Hypertensionmentioning
confidence: 99%